A rare case of bilateral cervical vagal neurofibromas: role of high-resolution ultrasound. Issue 1 (December 2017) - Liu, Bin; Zhang, Yuanding; Zhang, Lili; Zhang, Fan; Li, Hongyu; Li, Shuang; Liu, Yafang; Du, Jie; Zhao, Lirong
Abstract Background Neurofibromas originating from vagus nerves are rarely reported in the literature. In particular, plexiform neurofibromas of the bilateral cervical vagus nerve are extremely rare. Case presentation A 21-year-old female presented with a 2-year history of swelling on the right side of her neck. Physical examination revealed a soft-tissue mass on the right side of her neck. Ultrasonography (US) and magnetic resonance (MR) imaging showed a tumor centered in the right carotid sheath between the internal jugular vein and the common carotid artery. In addition, a similar nodular mass in the left carotid sheath was detected on US. The right mass was surgically resected; histopathological examination revealed a neurofibroma. Conclusions US can be a valuable method for preoperative evaluation of cervical mass, as it is capable of displaying the vagus nerve and provides sufficient diagnostic information. The cervical vagal neurofibroma can manifest as solitary or multifocal lesion. Bilateral neurofibromas are usually associated with neurofibromatosis type 1 (NF1). Early diagnosis and prompt surgical treatment should be considered.